(untitled) (REMUNOM, 2026)
Digestive physiology is commonly interpreted through biochemical frameworks centered on enzyme activity and nutrient metabolism. However, the physicochemical environment in which digestion occurs, particularly the rheological transformation of ingested food into chime, remains comparatively underexplored. A persistent assumption in nutritional discourse suggests that water intake during meals dilutes gastric acid and may impair digestion. This study critically examines this assumption by analyzing the role of periprandial hydration as a physicochemical factor influencing digestive processes. The main objective was to evaluate how hydration conditions affect chyme rheology and the kinetics of enzymatic hydrolysis during the digestion of solid foods. An integrative literature review was conducted between November 2025 and February 2026 using four international databases. The search strategy combined descriptors related to gastric digestion, food structure, rheology, water activity, and gastric fluid dynamics. The initial search retrieved 315 publications, which were systematically screened according to predefined eligibility criteria. After sequential evaluation of titles, abstracts, and full texts, 30 studies composed the final analytical corpus. The synthesis of evidence indicated that hydration influences digestion through multiple mechanisms. Adequate water availability reduces viscosity and enhances the mechanical dispersion of food particles, facilitating the formation of physiologically appropriate chyme. Hydration also increases water activity and molecular mobility within food matrices, improving enzymatic accessibility and reducing diffusion limitations during hydrolysis reactions. Conversely, poorly hydrated solid meals may impose additional mechanical and physiological demands on the digestive system. Overall, the findings suggest that periprandial hydration acts as a physicochemical modulator of digestive efficiency rather than a diluent of gastric acidity.